2018
DOI: 10.26905/jkdp.v22i2.2023
|View full text |Cite
|
Sign up to set email alerts
|

Does The Crude Palm Oil Market Walk Randomly?

Abstract: Study about the efficiency of the capital market has been extensively conducted, but it is still lack of research on the efficiency of another financial market such as commodity markets. This study specifically examines market efficiency in a weak form in the commodity market, especially in the crude palm oil (CPO) market. The purpose of this research is to analyze the weak form efficiency of the CPO market. Data used in this research is monthly CPO closing price data in 2010-2017 from Bursa Malaysia Derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Meanwhile, Abdalla (2012) conducted research on a day-to-the-week effect in the Indian capital market and concluded that there was no day-to-the-week effect. Another research on the commodity market, named the Crude Palm Oil (CPO) market, was conducted by Pulungan, Wahyudi, & Suharnomo (2018).…”
mentioning
confidence: 99%
“…Meanwhile, Abdalla (2012) conducted research on a day-to-the-week effect in the Indian capital market and concluded that there was no day-to-the-week effect. Another research on the commodity market, named the Crude Palm Oil (CPO) market, was conducted by Pulungan, Wahyudi, & Suharnomo (2018).…”
mentioning
confidence: 99%
“…Most of the research only aims to determine the efficiency of the capital market, so it is necessary to carry out further studies by adding several commodities as research objects. So that this research can provide an overview of market efficiency that is broader than previous research, such as the research of Pulungan [25] which examines the market efficiency of palm oil commodities. The existence of this research is also to complement the results of Chang [5] and Charles [6] research which discusses the market efficiency of the weak form of precious metals.…”
Section: Introductionmentioning
confidence: 99%